Profiling of small RNAs derived from tomato brown rugose fruit virus in infected Solanum lycopersicum plants by deep sequencing - Chen, Mangle; Wang, Donghai; Yang, Jiali; Cao, Yuhao; Song, Xuemei; Lu, Yuwen; Zheng, Hongying; Peng, Jiejun; Wu, Guanwei; Wu, Jian; Li, Junmin; Chen, Jianping; et al. (Frontiers in Microbiology, 2025)
Tomato brown rugose fruit virus (ToBRFV) is an emerging, rapidly spreading virus belonging to the genus Tobamovirus which seriously decreases tomato yields. RNA silencing is an evolutionarily conserved antiviral mechanism. In virus-infected plants, virus-derived small interfering RNAs (vsiRNAs) are one of the key components involved in the RNA silencing-based antiviral activity in plants. The main function of vsiRNAs is to target and degrade viral RNA. Studies have found that some vsiRNAs can also target host transcripts, further regulating host responses and symptoms and promoting viral survival and spread. In this study, the vsiRNA profiles of ToBRFV-infected tomato plants were obtained by deep sequencing. VsiRNAs were mainly 21 and 22 nucleotides in length and had a U-bias at the 5′ end. The single-nucleotide resolution profile shows that vsiRNAs exhibit a heterogeneous continuous distribution in the ToBRFV genomic RNA, with hotspot regions on the antisense strand located at the 5′ end of the RdRP and in the coding regions of MP and CP. The presence of vsiRNAs was confirmed in tomato plants infected with ToBRFV through RT-PCR, and GO and KEGG enrichment analyses were performed on the predicted vsiRNA target genes (with an expectation value less than or equal to 2.5). Seven potential target genes were selected for qRT-PCR analysis, confirming that their transcript accumulation significantly decreased in the leaves of tomato plants infected with ToBRFV. These genes may play an important role in the process of viral infection in tomatoes. Our results suggest a role for vsiRNAs in the ToBRFV–tomato interaction.